Optimizing lunar regolith beneficiation for ilmenite enrichment - Kulkarni, Kunal; Fabien Franke, Michel; Jundullah Hanafi, Muchammad Izzuddin; Gesing, Thorsten M.; Zabel, Paul (Frontiers in Space Technologies, 2024)
Over the past few years, the international space industry has focused extensively on advancing technologies to enable prolonged human space exploration missions. The primary limiting factor for these endeavors is the spacecraft’s capacity to transport and store essential supplies from Earth to support human life and mission equipment throughout the mission’s duration. In-situ resource utilization (ISRU) is the preferred solution for this challenge. Previous lunar missions have identified the presence of oxygen within the lunar regolith, which is an important resource for human space exploration missions. Oxygen is present in many different minerals within the lunar regolith out of which, ilmenite provides the highest yield of oxygen per unit mass using hydrogen reduction. However, the distribution of ilmenite is neither high nor uniform throughout the lunar surface and therefore, needs beneficiation, which is an important intermediate step for ilmenite-based oxygen production. A regolith beneficiation testbed was developed at DLR Bremen which is a TRL 4 level representation of the technology. The testbed has multiple process parameters that can be adjusted to produce the desired feedstock. This work focuses on the optimization of this testbed to produce a feedstock with higher ilmenite content than the input regolith. The testbed comprises three beneficiation techniques, viz. gravitational, magnetic and electrostatic beneficiation that work sequentially to produce the desired feedstock. The optimized parameter configuration achieved up to three-fold increase in the ilmenite grade relative to the input with about 32 wt% of the total ilmenite being recovered in the enriched output. These experiments have highlighted other underlying factors that influenced the experimental research such as the design of testbed components, system residuals and limited availability for Off-the-shelf components. The observations made from these experiments have also provided insights into the further development of the technology. The work has thus produced evidence for the effectiveness of the beneficiation testbed in producing an enriched feedstock while outlining avenues for future improvements.